The Effectiveness of Self-Control Training in Improving Interpersonal Skills, and Educational Performance of Adolescent Girls - Afrookhteh , Leila; Parsa moein , Koroush; Ghorban Jahromi , Reza (Applied Family Therapy Journal (AFTJ), 2020)
Aim: The present study aimed to determine the effectiveness of self-control training in improving interpersonal skills, and educational performance of adolescent girls. Method: The study was quasi-experimental with a pretest-posttest design, a control group, and a two-month follow-up. The statistical population consisted of female high school students in District 11 of Tehran, and 60 students were selected by the convenience sampling method and were randomly assigned into experimental (n=30), and control (n=30) groups. The research tools included Matson’s Interpersonal Communication Skills Questionnaire (1983), and the Educational Performance Questionnaire by Fam and Taylor (1999). The experimental group underwent self-control training for seven 60-minute sessions, and the control group waited for training during this period. Data were analyzed using repeated-measures analysis of variance. Results: The results indicated that self-control training was effective in improving interpersonal skills (F=11.92, P=0.001), and educational performance (F=19.14, P=0.001), and the effect was stable in the follow-up phase. Conclusion: Self-control training can be used as a useful intervention method to increase interpersonal skills and educational performance and thus better efficiency in students.